A composite lightweight aggregate and preparation method thereof

By filling and modifying wood powder on waste wood and sponge in large pieces of garbage, combined with the dual wrapping process, the problem of unreasonable grading and poor combination of waste when used in building materials is solved, and efficient resource utilization and multifunctional performance improvement of composite light aggregates is achieved.

CN119750940APending Publication Date: 2025-04-04HUIZHOU DAYAWAN HABITAT TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411938816.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The prior art is difficult to effectively solve the problems of unreasonable granule grading and poor bonding when used in building materials, which limits their application in a wider range of fields.

Method used

By innovatively utilizing waste wood and sponges in large waste, using wood powder to fill sponge pores, optimizing particle grading, and improving the mechanical properties of the material and sound absorption and sound insulation effect through strong alkali modification and double wrapping processes.

Benefits of technology

The resource utilization of waste has been realized, the density, mechanical properties and sound absorption and sound insulation of composite light aggregates have been improved, and the demand for multiple functional materials in modern buildings is met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119750940A_ABST
    Figure CN119750940A_ABST
Patent Text Reader

Abstract

The present invention provides a composite lightweight aggregate and a preparation method thereof. The composite lightweight aggregate comprises a core particle, the outer surface of the core particle is covered with an outer shell layer, the core particle comprises a wood powder sponge composite particle and an inner shell layer wrapping the wood powder sponge composite particle, in the wood powder sponge composite particle, wood powder is filled in the pores of the sponge particle. The present invention also provides a preparation method of the composite lightweight aggregate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite materials, and particularly relates to a composite lightweight aggregate and a preparation method thereof. Background Art

[0002] With the rapid advancement of urbanization, the living standards of urban residents are constantly improving, and the amount of waste generated is also increasing sharply. Among them, large-scale garbage (such as discarded furniture, old household appliances, etc.) as an important part of domestic waste, its treatment problem has attracted widespread attention. In particular, the wood and sponge used in large quantities in discarded furniture, as their service life increases, not only occupy a large amount of urban waste treatment space, but also due to their large size, the recycling and treatment costs are high. Traditional waste disposal methods are often unable to effectively solve the problems of resource waste and environmental pollution. Due to their unique physical and chemical properties, the recycling and utilization of these two wastes are difficult. There is an urgent need to find efficient and environmentally friendly recycling technologies and resource utilization paths to achieve waste reduction, resource utilization and harmless treatment.

[0003] Traditional methods of handling large pieces of garbage mainly include landfilling and incineration. Although these methods can handle waste, they also bring a considerable environmental burden. Landfilling not only occupies a large amount of land resources, but also seriously pollutes groundwater sources with leachate; incineration releases a large amount of harmful gases, causing air pollution, especially for wood and sponge waste. During the combustion process, a large amount of toxic gases such as dioxins may be produced, which seriously affect the air quality and ecological environment. Therefore, the development of more environmentally friendly waste recycling and utilization technologies, especially high-value utilization technologies for wood and sponges, has become a key issue that needs to be solved urgently. In the existing technology, most recycling methods focus on the initial processing of waste, such as crushing, sorting, etc., or for incineration power generation. The resource utilization of wood and sponges is still in its early stages, and a technical solution that can effectively increase their added value and combine well with other building materials has not yet been developed.

[0004] After the waste wood is crushed, wood powder can be obtained. This wood powder has the characteristics of light weight and strong adsorption, and has certain application potential in some fields. However, the particle gradation of wood powder is relatively simple, and the particle size distribution is uneven, which can easily lead to an increase in the internal porosity of building materials, thereby affecting the density and mechanical properties of building materials. In addition, as a lightweight material, although waste sponge has a low density and strong sound insulation and sound absorption effects, due to its own hydrophobicity and buoyancy, it is often difficult to form a good bond with substrates such as cement, limiting its application in building materials. Existing technologies are difficult to effectively solve the problems of unreasonable particle gradation and poor bonding when wood and sponge are used in building materials, which restricts their application in a wider range of fields. Therefore, how to effectively improve the physical and chemical properties of waste wood and waste sponge so that they can play a better role in building materials has become a technical problem that needs to be solved urgently. Summary of the Invention

[0005] The present invention aims to address at least one of the aforementioned technical problems existing in the prior art. To this end, the present invention provides a composite lightweight aggregate that innovatively utilizes waste wood and sponge from bulky waste, effectively improving the properties of the waste and achieving resource utilization. This composite aggregate matches the primary composition ratio of wood to sponge in bulky waste, maximizing waste utilization and reducing environmental pollution.

[0006] The invention also provides a method for preparing the composite lightweight aggregate.

[0007] The first aspect of the present invention provides a composite lightweight aggregate, comprising core particles, the outer surface of which is covered with an outer shell layer, the core particles comprising wood powder sponge composite particles and an inner shell layer wrapping the wood powder sponge composite particles, wherein wood powder is filled in the pores of the sponge particles.

[0008] One of the technical solutions of the present invention regarding composite lightweight aggregate has at least the following beneficial effects:

[0009] This invention innovatively utilizes waste wood and sponge from bulky garbage, effectively improving the properties of the waste and achieving resource utilization. It matches the main component ratio of wood and sponge in bulky garbage, maximizes waste utilization, and reduces environmental pollution.

[0010] By filling the pores of larger sponge particles with fine wood flour, this invention optimizes particle gradation, effectively reducing porosity and increasing the density of the composite lightweight aggregate. This optimized particle ratio and controlled wet mix moisture ensures sufficient penetration of the wood flour, further enhancing the material's mechanical properties and stability.

[0011] The composite lightweight aggregate, through its core of sponge and wood flour, achieves significant absorption of mid- and high-frequency noise. The outer shell, a high-density hardened layer, enhances the material's rigidity and quality, resulting in excellent sound insulation performance against low-frequency noise. This design effectively meets the demand for multifunctional materials in modern architecture, particularly in terms of achieving a good balance of performance in terms of both sound insulation and absorption.

[0012] According to some embodiments of the present invention, in the wood flour-sponge composite particles, the mass ratio of the wood flour to the sponge particles is 2 to 4:1.

[0013] The mass ratio of wood flour to sponge particles is 2 to 4:1, optimizing the particle structure and gradation of the composite lightweight aggregate, enhancing the material's density, mechanical properties, and stability. This ratio effectively fills the sponge's pores with wood flour, reducing porosity and improving the balance between sound insulation and absorption, with particular excellence in absorbing mid- and high-frequency noise and isolating low-frequency noise. Furthermore, this ratio helps maintain the material's lightweight properties, reducing the load on buildings, and improving both environmental and economic efficiency by reusing waste wood and sponge.

[0014] According to some embodiments of the present invention, the particle size of the wood powder is ≤1.18 mm.

[0015] Wood flour with a particle size of ≤1.18mm improves filling and uniformity, optimizes the structure and density of composite lightweight aggregate, and enhances the material's mechanical properties and stability. Fine particles improve the wet mix process, prevent clumping, and enhance sound absorption and insulation, particularly for mid- and high-frequency noise. Furthermore, fine wood flour better bonds with the cement matrix, enhancing the material's adhesion and contributing to the efficient resource utilization of waste wood, improving environmental friendliness and production efficiency.

[0016] According to some embodiments of the present invention, the particle size of the sponge particles is ≤4.75 mm.

[0017] A sponge particle size of ≤4.75mm helps optimize the particle size distribution of composite lightweight aggregate, improving the material's density and mechanical properties, particularly enhancing the sound absorption of mid- and high-frequency noise. This smaller particle size maintains the sponge's lightweight properties, reduces material weight, and improves processing and construction performance, resulting in a more uniform and efficient composite lightweight aggregate production process. Furthermore, this particle size design facilitates the resource utilization of waste sponge, reducing environmental burden and meeting the needs of sustainable development.

[0018] A second aspect of the present invention provides a method for preparing a composite lightweight aggregate, comprising the following steps:

[0019] S1: mixing wood flour and sponge particles, and adding water during the stirring process to facilitate the wood flour to fill the pores of the sponge particles, thereby obtaining wood flour sponge composite particles;

[0020] S2: soaking the wood flour-sponge composite particles in a strong alkaline solution to obtain modified composite particles;

[0021] S3: wrapping the modified composite particles with the first mineral powder slurry to form core particles, and spraying a strong alkaline solution after wrapping to obtain hardened core particles;

[0022] S4: wrapping the hardened core particles with a second mineral powder slurry to form a composite lightweight aggregate;

[0023] The solid content of the first mineral powder slurry is less than that of the second mineral powder slurry.

[0024] A technical solution in the method for preparing composite lightweight aggregate of the present invention has at least the following beneficial effects:

[0025] The present invention proposes an innovative technical solution, which transforms waste wood and waste sponge into composite lightweight aggregate with excellent comprehensive performance through alkali-activated modification and particle grading optimization technology. This technical solution improves the surface properties of waste wood and waste sponge by modifying them and optimizing the particle grading so that they can better bond with the cement matrix, thereby improving the mechanical properties and stability of the building materials. At the same time, the modified waste wood and sponge not only maintain excellent properties such as light weight, sound insulation, and sound absorption, but also effectively solve the problems of particle stratification and poor bonding in traditional processes. This technology not only improves the efficiency of resource utilization and reduces waste treatment costs, but also gives building materials multifunctionality, giving them a wider range of application prospects in the construction field. Through the application of this innovative technology, the resource utilization of large-scale garbage can be realized, thereby providing a new and sustainable development solution for the environmental protection industry.

[0026] The composite lightweight aggregate preparation method of the present invention significantly improves the mechanical properties, stability, and sound absorption and sound insulation of the particles by optimizing the combination of wood flour and sponge particles, strong alkali modification, and a double coating process. Filling the sponge pores with wood flour increases the density and binding strength of the particles, while modification with a strong alkali solution enhances the adhesion of the particles to the cement matrix. The double-layer mineral powder slurry coating process improves the uniformity and strength of the particles, and by controlling the solid content differences of the mineral powder slurry, the density of the outer shell layer is ensured. This method not only improves material performance, but also optimizes the production process, reduces resource waste, and meets environmental protection and sustainable development requirements.

[0027] According to some embodiments of the present invention, the solid content of the first mineral powder slurry is 15% to 25%.

[0028] A solids content of 15% to 25% in the first mineral powder slurry helps control the uniformity and thickness of the coating, avoiding excessively thick or uneven coatings, thereby improving the stability and mechanical properties of the composite particles. The slurry can penetrate and fill the tiny pores on and within the particles, effectively reducing porosity and enhancing density, providing a stable foundation for subsequent outer shell coating. This moderate solids content improves the mineral powder slurry's permeability and coating effectiveness, reduces excessive bonding and agglomeration, optimizes the production process, improves processing efficiency, and ensures high quality and consistency of the material.

[0029] According to some embodiments of the present invention, the solid content of the second mineral powder slurry is 40% to 60%.

[0030] A solids content of 40% to 60% in the second slurry helps form a dense and strong coating, significantly improving the strength, dimensional stability, and durability of the composite particles. This higher solids content enhances the hardening properties of the outer shell, enhancing the impact resistance, sound insulation, and long-term stability of the composite lightweight aggregate. It also optimizes production efficiency and ensures high material quality and consistency.

[0031] According to some embodiments of the present invention, the strong alkaline solution comprises a 3% to 7% sodium hydroxide solution.

[0032] A 3% to 7% sodium hydroxide solution in a strong alkaline solution effectively promotes the chemical modification of wood flour and sponge particles. It effectively corrodes their surfaces, destroying their hydrophobic functional groups and removing organic matter or contaminants attached to the surface, exposing more hydrophilic groups. This strengthens the bond between the particles and the cement matrix, optimizing the particle structure and pore characteristics. The sodium hydroxide solution increases the material's water absorption and reactivity, improving the mechanical properties, durability, and stability of the composite lightweight aggregate. It also promotes the resourceful utilization of waste, complying with environmental protection and sustainable development requirements.

[0033] According to some embodiments of the present invention, in step S3, after spraying the strong alkaline solution, the particles are sieved to adjust the uniformity and particle size distribution of the particles.

[0034] Screening the particles after spraying with a strong alkaline solution helps optimize particle uniformity and size distribution, improving the density, mechanical strength, and stability of the composite lightweight aggregate. Adjusting the particle size distribution enhances the material's sound absorption and insulation properties, improving construction performance and processing precision. Furthermore, the screening process ensures product consistency and controllability, increasing production efficiency and quality stability.

[0035] According to some embodiments of the present invention, in step S4, the hardened core particles are wrapped with a second mineral powder slurry, and the wrapping is performed in a rolling pan, and a strong alkaline solution is sprayed during the wrapping process.

[0036] Using a second mineral powder slurry to coat the hardened core particles in the rolling pan and spraying them with a strong alkaline solution helps form a uniform and dense coating, enhancing the composite particles' strength, dimensional stability, and impact resistance. The strong alkaline solution promotes the hardening and chemical bonding of the coating, improving sound insulation and durability. It also optimizes process uniformity and operational control, improving production efficiency and end-product quality. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 It is a flow chart of the preparation method of composite lightweight aggregate. DETAILED DESCRIPTION

[0038] The following are specific embodiments of the present invention, and the technical solutions of the present invention are further described in conjunction with the embodiments, but the present invention is not limited to these embodiments.

[0039] In a first aspect, some embodiments of the present invention provide a composite lightweight aggregate comprising core particles, wherein the outer surface of the core particles is covered with an outer shell layer, the core particles comprising wood powder sponge composite particles and an inner shell layer wrapping the wood powder sponge composite particles, wherein wood powder is filled in the pores of the sponge particles in the wood powder sponge composite particles.

[0040] It can be understood that the present invention effectively improves the performance of waste and realizes resource utilization by innovatively utilizing discarded wood and sponge in large-scale garbage. Since large-scale garbage is often composed of multiple materials and has a complex structure, low recycling value, and great difficulty in processing, its resource utilization has become a long-term technical problem. The present invention matches the main component ratio of wood and sponge in large-scale garbage, successfully utilizes them effectively into building materials, maximizes the utilization of waste, reduces environmental pollution, and opens up a new way for the treatment of large-scale garbage.

[0041] By filling the pores of larger sponge particles with fine wood flour, this invention optimizes particle gradation, effectively reducing porosity and increasing the density of the composite lightweight aggregate. Both sponge and wood flour are lightweight materials. While maintaining the lightweight properties of lightweight aggregate, this optimized particle ratio and controlled wet mix moisture content ensures sufficient penetration of the wood flour, further enhancing the material's mechanical properties and stability.

[0042] The composite lightweight aggregate, through its core of sponge and wood flour, achieves significant absorption of mid- and high-frequency noise. The outer shell, a high-density hardened layer, enhances the material's rigidity and quality, resulting in excellent sound insulation performance against low-frequency noise. This design effectively meets the demand for multifunctional materials in modern architecture, particularly in terms of achieving a good balance of performance in terms of both sound insulation and absorption.

[0043] In combination with the first aspect, in some embodiments of the present invention, in the wood flour-sponge composite particles, the mass ratio of wood flour to sponge particles is 2 to 4:1.

[0044] Specifically, the mass ratio of wood flour to sponge particles is 2 to 4:1, which has the following beneficial effects in the wood flour sponge composite particles:

[0045] 1. Optimizing Particle Structure and Performance: By establishing an optimal mass ratio of wood flour to sponge particles, the fine wood flour particles effectively fill the pores of the sponge particles, optimizing the gradation and internal structure of the composite particles and strengthening the bonding between the particles. This ratio ensures a more uniform and compact internal structure, contributing to improved mechanical properties and stability of the composite lightweight aggregate. A reasonable particle ratio maximizes the properties of both materials, enhancing the load-bearing capacity of the particles while achieving a good balance between mechanical properties and lightweight characteristics.

[0046] 2. Improving the density and strength of lightweight aggregate: A wood flour to sponge mass ratio of 2 to 4:1 can significantly reduce the porosity of the composite lightweight aggregate while avoiding the increased bulk density caused by excessive wood flour, thereby increasing the density of the material. This not only enhances the strength and compressive resistance of the composite particles, but also improves the dimensional stability of the material, helping to ensure its durability and reliability in practical applications.

[0047] 3. Enhanced Sound Insulation and Sound Absorption: The combination of wood flour's filling properties and the porous nature of sponge effectively enhances the composite lightweight aggregate's sound absorption and insulation capabilities. A wood flour to sponge particle mass ratio of 2 to 4:1 effectively balances the advantages of both. This ratio allows the wood flour to appropriately fill the sponge particle pores, reducing air vibrations within these pores and enhancing the absorption of mid- and high-frequency noise. The appropriate amount of sponge particles maintains the material's porous nature, helping to disperse and capture sound waves and enhance sound absorption. This ratio ensures that the composite particles offer excellent performance in both absorbing mid- and high-frequency noise and isolating low-frequency noise, meeting the diverse sound control requirements of building materials.

[0048] 4. Reducing Overall Weight and Improving Cost-Effectiveness: Sponge and wood are the two materials that make up the largest volume of bulky waste. Sponge is lightweight and porous, while the addition of wood flour helps maintain or enhance the structural strength of the composite lightweight aggregate. By adjusting the ratio of wood flour to sponge, the lightweight properties of the lightweight aggregate are maintained while effectively reducing the weight of the material, thereby helping to reduce the load on the building. This not only reduces transportation and construction costs, improving cost-effectiveness, but also enhances material performance, achieving efficient recycling of bulky waste and providing new ideas for the development of environmentally friendly building materials.

[0049] 5. Enhance the environmental friendliness of the material: Using wood powder and sponge as the core materials of the composite particles not only utilizes the environmentally friendly resources of waste wood and sponge, reducing the environmental burden, but also improves the overall performance of the composite lightweight aggregate through reasonable proportioning, promoting the construction industry's contribution to energy conservation, emission reduction and sustainable development.

[0050] As a result, the mass ratio of wood flour to sponge particles is 2 to 4:1, which optimizes the physical properties, sound absorption and sound insulation properties, structural stability and economy of the composite lightweight aggregate, and further enhances the application value of the material in the fields of construction and environmental protection.

[0051] In combination with the first aspect, in some embodiments of the present invention, the particle size of the wood powder is ≤1.18 mm.

[0052] Specifically, wood flour particle size ≤1.18mm has the following beneficial effects:

[0053] 1. Improve the filling and uniformity of wood flour: The smaller particle size enables wood flour to better fill the pores of sponge particles, optimizes the structure of composite particles, and makes the combination between wood flour and sponge particles tighter, thereby improving the overall density and stability of composite lightweight aggregate.

[0054] 2. Enhance the mechanical properties of the material: Fine wood powder particles have a larger specific surface area, which can better bond with the cement matrix, thereby enhancing the adhesion and mechanical strength of the composite material. This tiny particle structure helps to improve the compressive strength and impact resistance of the composite lightweight aggregate.

[0055] 3. Improved wet mixing process: Wood powder particle size ≤1.18mm makes the wet mixing process easier to control, allowing fine particles to be evenly distributed, avoiding uneven mixing or clumping caused by overly large wood powder. It is easier to achieve the ideal humidity and mixing effect, improving material production efficiency.

[0056] 4. Improved Sound Absorption and Insulation: The fine particle size of wood flour helps increase the porosity of the material, increasing the contact area between the wood flour and the sponge particles, and optimizing the composite particle's sound absorption, particularly for mid- and high-frequency noise. Furthermore, these fine particles help form a uniform, dense shell, enhancing sound insulation.

[0057] 5. Enhanced environmental protection and resource utilization: By using wood powder with a particle size of ≤1.18mm, we can maximize the use of waste wood resources and reduce wood waste. Fine wood powder particles can better combine with other components, improving material utilization efficiency and helping to achieve efficient resource utilization of waste.

[0058] Therefore, wood powder with a particle size of ≤1.18mm in composite lightweight aggregate can help improve filling properties, mechanical properties, sound absorption and insulation effects, and production efficiency, while optimizing the wet mixing process and enhancing environmental protection.

[0059] In combination with the first aspect, in some embodiments of the present invention, the particle size of the sponge particles is ≤4.75 mm.

[0060] Specifically, sponge particle size ≤4.75mm has the following beneficial effects:

[0061] 1. Optimize particle gradation and structure: Smaller sponge particles can better combine with wood powder particles, fill the gaps between wood powder particles, optimize the gradation of composite particles, and enhance the overall stability and density of the particles. This helps improve the mechanical properties and compressive strength of the composite lightweight aggregate.

[0062] 2. Improved sound absorption: Sponge itself has a highly porous structure, and smaller particle sizes help increase its surface area, thereby enhancing the sound absorption capacity of the sponge particles. Sponge particles with a particle size of 4.75mm or less can form more pores in the composite material, providing more effective sound wave absorption channels, especially for mid- and high-frequency noise.

[0063] 3. Improve the lightweight properties of the material: The lightweight properties of sponge particles are better maintained when the particle size is ≤4.75mm, reducing the weight of the material and alleviating the burden on the building. Smaller particle sizes of sponge particles are evenly distributed in the composite material, helping to ensure the lightweight and high strength of the lightweight aggregate.

[0064] 4. Improved processing and construction performance: Smaller sponge particles are easier to handle during processing and can be more evenly mixed with other ingredients (such as wood flour), avoiding uneven processing or uneven material distribution caused by overly large particles. This helps improve the production efficiency and construction performance of composite lightweight aggregate.

[0065] 5. Enhanced environmental protection and sustainability: By using sponge particles with a particle size of ≤4.75mm, waste sponge materials can be better recycled, reducing waste accumulation and environmental pollution. This not only improves resource utilization but also meets the needs of sustainable development.

[0066] Therefore, sponge particle size ≤4.75mm can optimize the particle grading of composite lightweight aggregate, improve sound absorption performance, lightweight characteristics and mechanical properties, while improving processing and construction performance, and promote the resource utilization of sponge waste, with significant environmental benefits.

[0067] In the second aspect, some embodiments of the present invention provide a method for preparing composite lightweight aggregate, the process of which is as follows: Figure 1 As shown, the following steps are included:

[0068] S1: mixing wood flour and sponge particles, and adding water during the stirring process to facilitate the wood flour to fill the pores of the sponge particles, thereby obtaining wood flour sponge composite particles;

[0069] S2: soaking the wood flour-sponge composite particles in a strong alkaline solution to obtain modified composite particles;

[0070] S3: using the first mineral powder slurry to wrap the modified composite particles to form core particles, and spraying a strong alkaline solution after wrapping to obtain hardened core particles;

[0071] S4: using the second mineral powder slurry to wrap the hardened core particles to form a composite lightweight aggregate;

[0072] It can be understood that the present invention can effectively improve the overall structural density and bonding strength of the particles and improve the mechanical properties and compressive resistance of the composite lightweight aggregate by filling the pores of the sponge particles with wood flour to form wood flour sponge composite particles.

[0073] It should be noted that in step S1, water is added during the stirring process, and the specific amount of addition can be added according to the degree of wetting of the particles. To prevent the unwetted particles from causing excessive dust during the stirring process, a small amount of water can be placed in the agitator in advance to pre-wet the wall surface. Adding water during the stirring process is to facilitate the filling of the wood powder into the pores of the sponge particles. If the wood powder is wetted in advance, it is difficult to determine whether the added water is appropriate. Therefore, water can be added during the stirring process, and it can be observed while adding to see whether the particles are appropriately wet.

[0074] Furthermore, modifying the wood flour sponge composite particles by soaking them in a strong alkaline solution helps to improve the bonding strength between the wood flour and sponge particles, and increases the adhesion between the particles and the cement matrix through chemical modification, further improving the performance and stability of the composite particles.

[0075] Furthermore, the modified composite particles are coated with a first slurry of mineral powder to form core particles, which are then hardened by spraying a strong alkaline solution to form a dense outer shell. This process effectively improves the strength and dimensional stability of the core particles, reduces the gaps between particles, and further enhances the overall mechanical properties of the composite lightweight aggregate.

[0076] Furthermore, the coating effect of the second slurry further enhances the structural stability and strength of the composite lightweight aggregate. The lower solids content of the first slurry ensures a uniform and appropriately thick coating, while the higher solids content of the second slurry helps form a dense outer shell, thereby improving overall hardness and impact resistance.

[0077] It should be noted that the present invention can better control the quality and performance of composite lightweight aggregate through a two-step coating process and a differentiated design of two mineral powder slurries, ensuring its higher uniformity and stability during the production process, thereby improving production efficiency and reducing the occurrence of defective products.

[0078] The entire preparation process makes full use of waste wood and sponge materials. Through modification and wrapping processes, it maximizes the resource utilization of waste, meeting the requirements of environmental protection and sustainable development.

[0079] Therefore, the preparation method of the present invention not only improves the mechanical properties, stability and sound absorption and sound insulation effects of the composite lightweight aggregate by optimizing the particle combination, modification and packaging processes, but also optimizes the production process, improves efficiency, and promotes the efficient resource utilization of waste, and has good application prospects.

[0080] In conjunction with the second aspect, in some embodiments of the present invention, the wetted wood flour and sponge particles are mixed and stirred with appropriate wetting and stirring to ensure that the wood flour can smoothly enter the pores of the sponge particles. Fine wood flour is filled into the pores of the larger sponge particles to improve particle distribution, forming a gradation of less than or equal to 4.75 mm. The porosity is reduced from the original 45%-55% to 25%-35%, a decrease of approximately 10%, thereby improving the density and mechanical properties of the lightweight aggregate.

[0081] Among them, "moderately moist" means putting the wood powder into the blender first, and slowly adding water during the mixing process until the surface of the material is slightly moist. The specific amount of water to be added can be increased or decreased depending on whether the wood powder used at the time is easy to absorb water. Finally, add the sponge particles and mix and stir to allow the wood powder to enter the pores.

[0082] In combination with the second aspect, in some embodiments of the present invention, the solid content of the first mineral powder slurry is 15% to 25%.

[0083] It should be noted that a lower solid content (15% to 25%) helps to form a thinner and more uniform coating layer, avoiding the coating layer being too thick, which will cause the particles to adhere too strongly and affect the morphology and function of the particles. This ensures the uniformity of the surface coating of the composite particles and optimizes the structure of the particles. A moderate solid content can make it easier for the mineral powder slurry to penetrate into the surface and pores of the wood powder sponge composite particles, thereby achieving a better coating effect. The mineral powder slurry has better fluidity at a lower solid content, can more evenly coat the particles, and improve the consistency of the material. Excessively high solid content may cause the viscosity of the mineral powder slurry to be too high, easily forming an uneven or too thick coating layer, and even causing agglomeration between the particles. By controlling the solid content of the first mineral powder slurry within the range of 15% to 25%, such problems can be effectively avoided, ensuring the uniformity of the coating layer and the stability of the particles.

[0084] It should also be noted that the appropriate coating thickness and uniformity enable the core particles to form a tighter structure during the hardening process, thereby enhancing the compressive strength, stability and durability of the composite lightweight aggregate.

[0085] Therefore, controlling the solid content of the first mineral powder slurry at 15% to 25% helps maintain good operability during the production process, avoids processing difficulties caused by excessive thickness of the mineral powder slurry, and makes the packaging process more efficient, reduces material waste, and improves production efficiency.

[0086] In combination with the second aspect, in some embodiments of the present invention, the solid content of the second mineral powder slurry is 40% to 60%.

[0087] By using a high-solid content mineral powder slurry to wrap the hardened core particles, a strong protective layer can be formed on the outside of the hardened core particles, enhancing the dimensional stability of the composite particles, avoiding deformation or breakage of the particles due to external forces, and thus improving the durability of the composite lightweight aggregate.

[0088] In combination with the second aspect, in some embodiments of the present invention, the strong alkaline solution includes a 3% to 7% sodium hydroxide solution.

[0089] Sodium hydroxide solution reacts with organic matter on the surface of wood flour and sponge particles, breaking down their molecular structure and promoting surface modification. This strengthens their adhesion to the cement matrix and improves the overall bonding strength and stability of the composite particles. Sodium hydroxide solution also enhances the water absorption of wood flour and sponge, making them easier to combine with other materials (such as mineral powder slurry), thereby improving the mechanical properties of the composite lightweight aggregate. Furthermore, the alkalinity of sodium hydroxide helps to activate the active ingredients in the wood flour, increasing reaction efficiency.

[0090] Furthermore, treating the sponge particles with a strong alkaline solution can change their internal pore structure, making them more uniform and having better sound absorption properties. Furthermore, the sodium hydroxide can improve the structure of the wood powder, making it more suitable for filling the pores of the sponge particles and optimizing the gradation of the composite particles.

[0091] It should also be noted that the sodium hydroxide solution removes impurities from the surfaces of the wood flour and sponge, improving the surface purity of the composite particles. This enhances the durability and aging resistance of the composite lightweight aggregate, extending its service life. Furthermore, the strong alkaline solution corrodes the surfaces of the wood flour and sponge particles, increasing their surface roughness. This rough surface structure significantly improves the particles' hydrophilicity. This rough surface provides more contact points and binding sites, facilitating the adhesion and penetration of the mineral powder slurry, further improving the mechanical properties and stability of the composite lightweight aggregate.

[0092] Therefore, using sodium hydroxide solution to treat waste wood and sponge can effectively promote the resource utilization of waste, improve the performance of these waste materials through chemical modification, and enable them to be efficiently used in building materials, which is in line with environmental protection and sustainable development goals.

[0093] In combination with the second aspect, in some embodiments of the present invention, in step S3, after spraying the strong alkaline solution, the particles are sieved to adjust the uniformity and particle size distribution of the particles.

[0094] The screening process removes fine particles and oversized particles that do not meet the particle size requirements, ensuring a more uniform particle size distribution within the composite particles. This helps improve the overall performance of the composite lightweight aggregate, ensuring that each particle exhibits balanced mechanical properties and sound absorption.

[0095] Screening can optimize the gradation of composite particles, making the contact between particles closer, thereby improving the density, mechanical strength and stability of the material. A reasonable particle size distribution can reduce the gaps between particles, increase the density of the material, and improve its compressive strength and impact resistance.

[0096] The sieving process helps precisely adjust the particle size of the composite material, allowing particles of varying sizes to form a well-defined structure within the composite material, optimizing the material's sound absorption and insulation properties. A uniform particle size distribution provides more efficient sound absorption channels and enhances the material's sound insulation performance, particularly for mid- and high-frequency noise.

[0097] Improved particle uniformity after screening can make subsequent construction and processing smoother. Particle consistency helps improve the uniformity of the mixing process, reduce unstable factors during construction, and improve the quality and production efficiency of composite lightweight aggregate.

[0098] The sieved particles have a more consistent size and morphology, which helps control the final quality of the composite lightweight aggregate, ensures stable product performance, avoids uneven particle distribution, and improves the reliability and service life of the overall material.

[0099] In conjunction with the second aspect, in some embodiments of the present invention, the screening standard is to use a 4.75 mm standard sieve to screen out particles smaller than 4.75 mm. Screening can effectively remove excessively fine particles, avoid excessive material density or uneven performance, and maintain a suitable particle size distribution.

[0100] In combination with the second aspect, in some embodiments of the present invention, in step S4, the hardened core particles are wrapped with a second mineral powder slurry, and the wrapping is performed in a rolling pan, and a strong alkaline solution is sprayed during the wrapping process.

[0101] Using a second mineral powder slurry to coat the hardened core particles in the rolling pan and spraying them with a strong alkaline solution helps form a uniform and dense coating, enhancing the composite particles' strength, dimensional stability, and impact resistance. The strong alkaline solution promotes the hardening and chemical bonding of the coating, improving sound insulation and durability. It also optimizes process uniformity and operational control, improving production efficiency and end-product quality.

[0102] The following will clearly and completely describe the concept and technical effects of the present invention in conjunction with the embodiments to fully understand the purpose, features and effects of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0103] In the description of the present invention, reference to terms such as "one embodiment," "some embodiments," "illustrative embodiments," "examples," "specific examples," or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the exemplary expressions of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in any one or more embodiments or examples.

[0104] Unless otherwise specified, "room temperature" in the present invention means 25°C±5°C.

[0105] Unless otherwise specified, “about” in the present invention means that the allowable error is within ±2%.

[0106] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or those recommended by the manufacturer. All reagents or instruments used, if the manufacturer is not specified, are commercially available conventional products.

[0107] In the embodiment, gradation refers to the distribution of particles of different aggregate sizes, which can be determined by sieve analysis. A gradation of less than or equal to 4.75 mm means that the particle size is ≤4.75 mm.

[0108] Mineral powder is the abbreviation of granulated blast furnace slag powder. It is a commonly used admixture in the building materials industry. S95 grade mineral powder can be used.

[0109] Mineral powder, acting as an active material, generates CASH and NASH gels through alkali activation, providing strength and filling interparticle pores, improving density and durability. Sodium hydroxide solution not only initiates the alkali-activated reaction of the mineral powder but also modifies the wood flour-sponge particles, making them more susceptible to mineral powder adhesion. During the pan granulation process, spraying sodium hydroxide solution (the pre-soaking solution can be used directly here) further promotes mineral powder encapsulation, enhancing the strength and uniformity of the particles.

[0110] Example 1

[0111] A composite lightweight aggregate was prepared, and the specific steps were as follows:

[0112] 1. Particle grading optimization

[0113] Waste wood is crushed into wood flour with a particle size of ≤1.18mm, and waste sponge is crushed into particles with a size of ≤4.75mm. After mixing the wood flour and sponge particles in a ratio of 2:1, proper wetting and stirring are performed to ensure that the wood flour can easily enter the pores of the sponge particles. The fine wood flour is then filled into the pores of the larger sponge particles to improve particle distribution, resulting in a gradation of less than or equal to 4.75mm. This reduces the porosity from the original 51% to 41%, improving the density and mechanical properties of the lightweight aggregate.

[0114] Among them, "moderately moist" means putting the wood powder into the blender first, and slowly adding water during the mixing process until the surface of the material is slightly moist. The specific amount of water to be added can be increased or decreased depending on whether the wood powder used at the time is easy to absorb water. Finally, add the sponge particles and mix and stir to allow the wood powder to enter the pores.

[0115] 2. Particle modification

[0116] After repeated mixing, the mixture was immersed in a sodium hydroxide solution with a concentration of 5% for 30 minutes to promote the modification of the material and improve its hydrophilicity and bonding with the slurry.

[0117] 3. Secondary packaging and step-by-step granulation process

[0118] First, a thin slurry (mineral powder solid content 20%) is used to wrap the sponge and wood flour mixture to form preliminary particles; the mixed particles wrapped with the thin slurry are placed in a rolling pan and rolled, sprayed with 5% sodium hydroxide solution, and the hardening process is accelerated by alkali excitation technology. Fine particles are then removed by screening to adjust the uniformity and particle size distribution of the particles; finally, a thick slurry (mineral powder solid content 50%) is used to wrap the surface in a rolling pan and sprayed with 5% sodium hydroxide solution to further enhance the strength and dimensional stability of the particles, ensuring the consistency of the lightweight aggregate performance and the density of the structure.

[0119] Example 2

[0120] A composite lightweight aggregate was prepared, and the specific steps were as follows:

[0121] 1. Particle grading optimization

[0122] Waste wood is crushed into wood flour with a particle size of ≤1.18mm, and waste sponge is crushed into particles with a size of ≤4.75mm. After mixing wood flour and sponge particles in a ratio of 3:1, moderate wetting and stirring are performed to ensure that the wood flour can easily enter the pores of the sponge particles. The fine wood flour is then filled into the pores of the larger sponge particles to improve particle distribution, resulting in a gradation of less than or equal to 4.75mm. This reduces the porosity from the original 48% to 35%, improving the density and mechanical properties of the lightweight aggregate.

[0123] 2. Modification of mixed particles

[0124] After repeated mixing, the mixture was immersed in a sodium hydroxide solution with a concentration of 4% for 30 minutes to promote the modification of the material and improve its hydrophilicity and binding properties with the slurry.

[0125] 3. Secondary packaging and step-by-step granulation process

[0126] First, a thin slurry (mineral powder solid content 25%) is used to wrap the sponge and wood flour mixture to form preliminary particles; the mixed particles wrapped with the thin slurry are placed in a rolling pan and rolled, sprayed with 4% sodium hydroxide solution, and the hardening process is accelerated by alkali excitation technology. Fine particles are then removed by screening to adjust the uniformity and particle size distribution of the particles; finally, a concentrated slurry (mineral powder solid content 55%) is used to wrap the surface in a rolling pan and sprayed with 4% sodium hydroxide solution to further enhance the strength and dimensional stability of the particles, ensuring the consistency of the lightweight aggregate performance and the density of the structure.

[0127] Example 3

[0128] A composite lightweight aggregate was prepared, and the specific steps were as follows:

[0129] 1. Crushing waste wood into wood flour with a particle size of ≤1.18mm, and crushing waste sponge into particles with a size of ≤4.75mm. Mix the wood flour and sponge particles in a 4:1 ratio, then gently wet and stir to ensure the wood flour can easily penetrate the pores of the sponge particles. Filling the pores of the larger sponge particles with fine wood flour improves particle distribution, creating a gradation of less than or equal to 4.75mm. This reduces the porosity from the original 49% to 32%, improving the density and mechanical properties of the lightweight aggregate.

[0130] 2. Particle grading optimization

[0131] After repeated mixing, the mixture was immersed in a sodium hydroxide solution with a concentration of 5% for 30 minutes to promote the modification of the material and improve its hydrophilicity and bonding with the slurry.

[0132] 3. Secondary packaging and step-by-step granulation process

[0133] First, a thin slurry (30% mineral powder solid content) is used to wrap the sponge and wood flour mixture to form preliminary particles; the mixed particles wrapped with the thin slurry are placed in a rolling pan and rolled, sprayed with 5% sodium hydroxide solution, and the hardening process is accelerated by alkali excitation technology. Fine particles are then removed by screening to adjust the uniformity and particle size distribution of the particles; finally, a thick slurry (60% mineral powder solid content) is used for surface wrapping in a rolling pan and sprayed with 5% sodium hydroxide solution to further enhance the strength and dimensional stability of the particles, ensuring the consistency of the lightweight aggregate performance and the density of the structure.

[0134] Comparative Example 1

[0135] A composite lightweight aggregate was prepared. This composite aggregate differs from Example 1 in that, in Step 1, the wood flour and sponge particles were not modified with a sodium hydroxide solution; instead, the process proceeded directly to particle size optimization and subsequent granulation. This omission of the modification step resulted in poor hydrophilicity and poor binding properties of the wood flour and sponge particles with the mineral powder slurry, significantly reducing the strength and density of the resulting lightweight aggregate.

[0136] Comparative Example 2

[0137] A composite lightweight aggregate was prepared. This differed from Example 1 in that, in Step 3, a concentrated slurry (mineral powder slurry with a solids content of 30%) was directly used to coat the wood flour and sponge mixture, and the dilute slurry coating and alkali-induced hardening steps were omitted. The lack of separate granulation and hardening processes resulted in uneven particle size distribution and incomplete surface coating, ultimately resulting in insufficient dimensional stability and mechanical properties for the lightweight aggregate.

[0138] Performance Testing

[0139] The strength, bulk density, and sound absorption and sound insulation properties of the composite lightweight aggregates prepared in the examples and comparative examples were tested. Specific test methods refer to relevant standards:

[0140] Cylinder compression strength: GB / T17431.2-2010 "Light aggregate and its test methods Part 2: Light aggregate test methods" is used to measure the compressive capacity of lightweight aggregate and reflect its mechanical properties.

[0141] Bulk density: GB / T17431.2-2010 "Lightweight aggregate and its test methods Part 2: Lightweight aggregate test methods" is used to measure the mass of lightweight aggregate per unit volume, reflecting its density and filling performance.

[0142] Sound absorption performance: The sound absorption performance of composite lightweight aggregate is tested using GB / T20247-2006 "Acoustic Reverberation Chamber Sound Absorption Measurement" and its sound absorption performance grade is evaluated with reference to GB / T16731-2023 "Sound Absorption Performance Classification of Building Sound-Absorbing Products".

[0143] Sound insulation performance: Referring to GB / T19889.3-2005 "Acoustic sound insulation measurement of buildings and building elements Part 3: Laboratory measurement of airborne sound insulation of building elements", the sound insulation value of composite lightweight aggregate is measured and its sound insulation effect is evaluated.

[0144] The results are shown in Table 1.

[0145] Table 1

[0146]

[0147]

[0148] As can be seen from the data in Table 1, the composite lightweight aggregates of Examples 1, 2, and 3 are significantly superior to those of Comparative Examples 1 and 2 in terms of cylinder compressive strength, bulk density, sound absorption, and sound insulation. These differences reflect the effects of different preparation processes on the properties of the composite lightweight aggregates.

[0149] Cylinder pressure strength:

[0150] Example 1 (3.5 MPa), Example 2 (3.6 MPa), and Example 3 (3.8 MPa) have higher cylinder compressive strengths than Comparative Example 1 (2.8 MPa) and Comparative Example 2 (3.1 MPa). This indicates that the mechanical properties of the composite lightweight aggregate have been significantly enhanced after treatment with sodium hydroxide solution modification, step-by-step coating of dilute and concentrated slurries, and alkali-activated hardening.

[0151] Bulk density:

[0152] The bulk density of Example 1, Example 2 and Example 3 is 650 kg / m 3 、670kg / m 3 and 720kg / m 3 , significantly higher than comparative example 1 (600kg / m 3 ) and Comparative Example 2 (620 kg / m 3 This shows that by optimizing particle grading, adopting wet mixing and modification treatment, the density of composite lightweight aggregate is improved, the particle distribution is more uniform, the void ratio is reduced, and the material is more compact and stable.

[0153] Sound absorption performance:

[0154] In terms of sound absorption performance, the lightweight aggregate of Example 1 achieved Class B, Example 2 achieved Class C, and Example 3 achieved Class D. Comparative Examples 1 and 2 both achieved Class C. This demonstrates that the sound absorption performance of the composite lightweight aggregate has been improved through the modification and step-by-step encapsulation process. In particular, Example 1, through optimized grading and modification, exhibits superior sound absorption.

[0155] Sound insulation:

[0156] In terms of sound insulation, Example 1 achieved 23dB, Example 2 achieved 26dB, and Example 3 achieved 28dB, while Comparative Example 1 achieved 19dB and Comparative Example 2 achieved 21dB. The refined processing significantly improved the sound insulation performance of the composite lightweight aggregate, with Example 3 in particular demonstrating optimal sound insulation performance.

[0157] In summary, Examples 1, 2, and 3 significantly improved the mechanical properties, density, sound absorption, and sound insulation of composite lightweight aggregate by employing sodium hydroxide solution modification, optimized particle size distribution, a step-by-step coating process, and alkali activation technology. These steps not only enhanced the material's strength and stability but also optimized its versatility in construction applications, achieving particularly good results in sound insulation.

[0158] Comparative Examples 1 and 2 lacked modification and a step-by-step packaging process, resulting in poor mechanical properties, density, and sound insulation of the lightweight aggregate. In particular, the lack of modification in Comparative Example 1 resulted in low cylinder compressive strength and bulk density, and poor sound absorption and insulation performance.

[0159] Therefore, the multi-step treatment in the embodiment, especially the sodium hydroxide solution modification and step-by-step coating process, plays a key role in improving the performance of the composite lightweight aggregate.

[0160] This invention develops a modified lightweight aggregate based on waste wood and sponge, solving the problems of bulky waste resource utilization and insufficient building material performance. Through strong alkali modification, particle grading optimization, and a multi-stage coating process, the lightweight aggregate's density, strength, and dimensional stability are improved. Wood powder and sponge form the core, while alkali-activated mineral powder forms the shell. The synergistic sound absorption and sound insulation properties are achieved internally and externally, achieving significant mid- and high-frequency sound absorption and low-frequency sound insulation. This invention achieves waste resource utilization, imparts lightweight and multifunctional building materials, and broadens its application areas.

[0161] The present invention has been described in detail above with reference to the embodiments. However, the present invention is not limited to the above embodiments. Various changes can be made within the scope of knowledge possessed by ordinary technicians in the relevant technical field without departing from the spirit of the present invention.

Claims

1. A composite lightweight aggregate, characterized in that: The invention comprises a core particle, the outer surface of which is covered with an outer shell layer, the core particle comprises a wood powder sponge composite particle and an inner shell layer wrapping the wood powder sponge composite particle, and in the wood powder sponge composite particle, wood powder is filled in the pores of the sponge particle.

2. The composite lightweight aggregate according to claim 1, characterized in that: In the wood powder sponge composite particles, the mass ratio of the wood powder to the sponge particles is 2 to 4:

1.

3. The composite lightweight aggregate according to claim 1 or 2, characterized in that: The particle size of the wood powder is ≤1.18 mm.

4. The composite lightweight aggregate according to claim 1 or 2, characterized in that: The particle size of the sponge particles is ≤4.75 mm.

5. A method for preparing the composite lightweight aggregate according to any one of claims 1 to 4, characterized in that: The steps include: S1: mixing wood powder and sponge particles, and adding water during the stirring process to make it easier for the wood powder to fill the pores of the sponge particles, thereby obtaining wood powder sponge composite particles; S2: soaking the wood flour sponge composite particles in a strong alkaline solution to obtain modified composite particles; S3: using the first mineral powder slurry to wrap the modified composite particles to form core particles, and spraying a strong alkaline solution after wrapping to obtain hardened core particles; S4: using a second mineral powder slurry to wrap the hardened core particles to form a composite lightweight aggregate; The solid content of the first mineral powder slurry is less than the solid content of the second mineral powder slurry.

6. The method according to claim 5, characterized in that The solid content of the first mineral powder slurry is 15% to 25%.

7. The method according to claim 5, characterized in that The solid content of the second mineral powder slurry is 40% to 60%.

8. The method according to claim 5, characterized in that The strong alkali solution includes 3% to 7% sodium hydroxide solution.

9. The method according to claim 5, characterized in that In step S3, after spraying the strong alkaline solution, the particles are screened to adjust the uniformity and particle size distribution of the particles.

10. The method according to claim 5, characterized in that In step S4, the hardened core particles are wrapped with a second mineral powder slurry in a rolling pan, and a strong alkaline solution is sprayed during the wrapping process.